KONTEKSTUALIASI KEDUDUKAN DAN PERAN PEREMPUAN DALAM KITAB TAQRIB - Nandang Abdurrohim; Hapid Ali (UIN Sunan Gunung Djati Bandung, 2019)
The position and role of women in has a common similarity with the jurisprudence discourses in Taqrib jurisprudence (Fiqh) with some spesific subjects as characteristics of the Syafi'iyyah jurisprudence (fiqh). In the matter of the position and role of women in the field of social (muamalah) and worship, Taqrib is the same as Sunni jurisprudence (fiqh) which places general equality in these positions and roles generally. In this study, the author used the method of content analysis (content analysis) as a measurement in exploring and obtaining data. From the results of these studies, it was found that some tees were related to the position of the women in taqrib jurisprudence, namely; In the law of marriage, fathers and grandfathers can force girls to marry without consent; in inheritance law, it is assumed that the relatives of the mother / daughter line are not entitled to inheritance at all even though the family members of the residuals (ashabah) are not present; the position of judge cannot be handled by a woman even though in the field of social (muamalah); and women only have the right to be witnesses on economic issues and special cases that can only understoodby them generally.Â